2023
DOI: 10.1021/acsnano.3c01469
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Temperature Operation of Lithium–Sulfur Batteries Enabled by Multi-Branched Vanadium Nitride Electrocatalyst

Abstract: High-performance lithium−sulfur (Li−S) batteries that can work normally under harsh conditions have attracted tremendous attention; however, the sluggish reaction kinetics of polysulfide conversions at low temperatures as well as the notorious polysulfide shuttling at high temperatures remain to be resolved. Herein, a multibranched vanadium nitride (MB-VN) electrocatalyst has been designed and deployed for Li−S batteries. Both experimental (time-of-flight secondary ion mass spectroscopy and adsorption tests) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The cells with the typical PP separator exhibited a lower discharge and charge capacity at the low temperature of −20 °C owing to the sluggish reaction kinetics. 44 The initial discharge specific capacity of the In 2 O 3 @C separator cell is 1007.8 mA h g −1 at 0.1C at −20 °C with the specific capacity retention of 798.8 mA h g −1 after 100 cycles, much higher than the cell with the PP separator (432 mA h g −1 ), which implied that the In 2 O 3 @ C interlayer maintained favorable stability and fast reaction conversion of LiPSs. In Figure 8b, a charge/discharge voltage profile comparison at 0.1C with different separators showed that the traditional PP separator has a large polarization voltage, especially in the range of soluble LiPSs to solid Li 2 S 2 and Li 2 S. In contrast, the cell with In 2 O 3 @C interlayer maintains relatively normal charge/discharge curves with whole cycle life (Figure 8c).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The cells with the typical PP separator exhibited a lower discharge and charge capacity at the low temperature of −20 °C owing to the sluggish reaction kinetics. 44 The initial discharge specific capacity of the In 2 O 3 @C separator cell is 1007.8 mA h g −1 at 0.1C at −20 °C with the specific capacity retention of 798.8 mA h g −1 after 100 cycles, much higher than the cell with the PP separator (432 mA h g −1 ), which implied that the In 2 O 3 @ C interlayer maintained favorable stability and fast reaction conversion of LiPSs. In Figure 8b, a charge/discharge voltage profile comparison at 0.1C with different separators showed that the traditional PP separator has a large polarization voltage, especially in the range of soluble LiPSs to solid Li 2 S 2 and Li 2 S. In contrast, the cell with In 2 O 3 @C interlayer maintains relatively normal charge/discharge curves with whole cycle life (Figure 8c).…”
Section: Resultsmentioning
confidence: 89%
“…The In 2 O 3 @C cell still shows superior performance in comparison to the cell with the PP separator. The cells with the typical PP separator exhibited a lower discharge and charge capacity at the low temperature of −20 °C owing to the sluggish reaction kinetics . The initial discharge specific capacity of the In 2 O 3 @C separator cell is 1007.8 mA h g –1 at 0.1C at −20 °C with the specific capacity retention of 798.8 mA h g –1 after 100 cycles, much higher than the cell with the PP separator (432 mA h g –1 ), which implied that the In 2 O 3 @C interlayer maintained favorable stability and fast reaction conversion of LiPSs.…”
Section: Resultsmentioning
confidence: 97%
“…The strategy we developed for coupling reactive Li 2 S with bi-directional electrocatalysts provides a new way to realize high-energy and wide-temperature LiÀ S batteries. Ma et al [84] design of polydendritic vanadium nitride as a catalyst to catalyze the conversion reaction of lithium polysulfide. In situ Raman spectroscopic characterization revealed that multidendritic vanadium nitride can significantly inhibit the shuttle effect of lithium polysulfide when used as a catalyst.…”
Section: Improved Cathodementioning
confidence: 99%
“…We analyzed the charge transfer resistance (R ct ) before cell cycling using EIS. The Li−S batteries with the CNP interlayer showed smaller R ct (20.53 Ω) than the Li−S batteries with PP separator (31.26 Ω), due to the higher electrical conductivity of the CNP interlayer 72 through counterion exchange, enabling the CNP interlayer to reactivate inactive sulfur as a secondary collector (Figure 7b and Table S4). 32 In addition, we assessed the ability of the CNP interlayer to mitigate the self-discharge behavior associated with the shuttle phenomenon.…”
Section: Electrochemical Analysis Of Cnp Interlayermentioning
confidence: 99%